Cryo-EM structure of the SARS coronavirus spike glycoprotein in complex with its host cell receptor ACE2 - Song, Wenfei; Gui, Miao; Wang, Xinquan; Xiang, Ye (PLOS Pathogens, 2018)
Author summary The global outbreak of SARS in 2002–2003 was caused by infection by a human coronavirus, SARS-CoV. Although the virus has been extensively studied with regard to epidemiology, virology, clinical features and other aspects, there are still no approved antiviral drugs and vaccines to treat and prevent infections of SARS-CoV. The spike (S) glycoprotein of the coronavirus, responsible for host cell attachment and mediating host cell membrane and viral membrane fusion during infection, is key to the viral life cycle and a major target for antiviral drugs and vaccines. In this study, we report the structures of different conformational states of the SARS-CoV S glycoprotein during virus entry. Specifically, we found that the S glycoprotein retains the prefusion trimer structure after trypsin cleavage and low-pH treatment. Additionally, binding with host cell receptor ACE2 promotes the release of S1 subunits from the S trimer and triggers the pre- to postfusion conformational transition. Our results provide new insights for understanding the mechanisms involved in coronavirus S glycoprotein-mediated virus entry.